2016
DOI: 10.1007/s11136-016-1353-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-year trajectories of global perceived quality of life for youth with chronic health conditions

Abstract: PurposeObjectives of this longitudinal study were to examine 3-year trajectories of global perceived quality of life (QOL) for youth with chronic health conditions, as obtained from youth and parent reports, and to identify personal and environmental factors associated with the trajectory groups for each perspective.MethodsYouth with various chronic conditions aged 11–17 years and one of their parents were recruited from eight children’s treatment centers. Latent class growth analysis was used to investigate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…28,31 Study results are congruent with recent cross-sectional studies that emphasize the relative impact of functional abilities and capabilities, as well as environmental qualities, on the child's involvement in home-based activities. Specifically, significant effects of functional capabilities and environmental support on children's involvement in meaningful daily life activities suggest the importance of targeting these areas during rehabilitation with this population.…”
Section: Home Participation Change After Discharge From the Picusupporting
confidence: 86%
See 3 more Smart Citations
“…28,31 Study results are congruent with recent cross-sectional studies that emphasize the relative impact of functional abilities and capabilities, as well as environmental qualities, on the child's involvement in home-based activities. Specifically, significant effects of functional capabilities and environmental support on children's involvement in meaningful daily life activities suggest the importance of targeting these areas during rehabilitation with this population.…”
Section: Home Participation Change After Discharge From the Picusupporting
confidence: 86%
“…Specifically, significant effects of functional capabilities and environmental support on children's involvement in meaningful daily life activities suggest the importance of targeting these areas during rehabilitation with this population. 28,31 Study results are congruent with recent cross-sectional studies that emphasize the relative impact of functional abilities and capabilities, as well as environmental qualities, on the child's involvement in home-based activities. 16,17 Clinically, these findings suggest multiple potential candidate targets for rehabilitation interventions with this population, namely environmental supports, or compensatory strategies, and functional abilities.…”
Section: Determinants Of Change In Home Participation After Critical supporting
confidence: 86%
See 2 more Smart Citations
“…Highlighting the importance of cultural context, spirituality-but not religious service attendance-was associated with higher subsequent LS within a sample of adolescents in Portugal . In addition, research from Canada has shown that youth with higher levels of spirituality are more likely to experience trajectories of high and stable LS than trajectories of moderate or low LS (McDougall et al, 2016). Interestingly, research in Hong Kong has found that adolescents who are higher in spirituality tend to experience sharper declines in LS than less spiritual adolescents (Shek & Liang, 2018).…”
Section: Are the Links Between Religion/spirituality And Life Satisfa...mentioning
confidence: 99%